2017
DOI: 10.1111/trf.14036
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing of bacterial infections transmitted through substances of human origin in Europe

Abstract: Six bacteria were defined as being of the highest priority in respect of the threat to the safety of SoHO and will be the subject of subsequent in-depth risk assessments to be conducted by ECDC to identify measures to mitigate the risk posed by these bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…5 In a recent study from the European Center for Disease Prevention and Control, E. coli ranks fourth among bacteria and second among Gram-negative bacteria. 35 In comparison, other Gram-negative bacteria as Serratia sp. ranked fourth in France and 10th in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In a recent study from the European Center for Disease Prevention and Control, E. coli ranks fourth among bacteria and second among Gram-negative bacteria. 35 In comparison, other Gram-negative bacteria as Serratia sp. ranked fourth in France and 10th in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In France E. coli represented the third bacterium and the first Gram‐negative bacterium responsible for TTBI . In a recent study from the European Center for Disease Prevention and Control, E. coli ranks fourth among bacteria and second among Gram‐negative bacteria . In comparison, other Gram‐negative bacteria as Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ranking of transfusion-transmitted bacteria considering several risk factors showed that all relevant pathogens except for Clostridium spp. can be cultivated under aerobic culture conditions [38]. In Europe, the screening of PC using a single aerobic bottle is implemented in Denmark (Fig.…”
Section: Anaerobic Screening – Is It Worth the Effort?mentioning
confidence: 99%
“…The residual risk of transmitting the major viruses hepatitis C virus, hepatitis B virus, and human immunodeficiency virus has been reduced to a minimum using nucleic amplification technologies and fourth‐generation serology screening tests . In the period 2010 to 2013, among the 96,798,000 blood components distributed, the European commission reported 111 transfusion‐transmitted infections in the European Union, including 73 bacterial (66%), 35 viral (32%), and 3 parasitic cases (<3%) . Bacterial contamination remains the highest residual infectious risk despite current preventive strategies …”
mentioning
confidence: 99%